GENETIC VARIANCE, CORRELATION AND HERITABILITY FOR GRAIN YIELD IN A MEDIUM-MATURING YELLOW-ENDOSPERM MAIZE POPULATION - Oyekunle, M.; Abdullahi, U. S.; Hassan, L. B.; Yahaya, M. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2018)
Information on the magnitude of additive relative to non-additive variance of a trait in a population helps in deciding the appropriate breeding strategies for improving such trait. Two hundred and fifty-five full-sib families derived from IARTZI-Y Pop DT STR C0 using North Carolina Design I were evaluated at three environments in 2017 to determine the magnitude of additive variance relative to other components of variance in the population, and to assess relationship between grain yield and other agronomic traits. A 17 × 15 alpha-lattice design with two replications was used in each trial after sub-dividing the males into 17 sets, each containing 15 full-sib families. Data collected were subjected to analysis of variance using appropriate software at P < 0.05. Males-within-set and females in male-within-set mean squares were significant (P < 0.01) for measured traits. Non-additive variances were larger than additive variances for grain yield and anthesis-silking interval but not for other traits, indicating the predominance of non-additive gene action for inheritance of grain yield in the population. The heritability estimates ranged between 1% for grain yield and 94% for ear height. Grain yield had significant positive genotypic correlations with days to mid-silk (rg = 0.75**) and number of ears per plant (rg = 0.26) but negative with husk cover (rg = -14*), anthesis-silking interval (rg = -0.11*), and ear aspect (rg = -22**). Recurrent selection schemes would be effective for improving yield-related traits while grain yield could be improved through hybrid development or by indirect selection through secondary traits.